Preparation of Naringenin Nanosuspension and Its Antitussive and Expectorant Effects - Zhengqi Dong; Rui Wang; Mingyue Wang; Zheng Meng; Xiaotong Wang; Meihua Han; Yifei Guo; Xiangtao Wang (Molecules, 2022)
Naringenin (NRG) is a natural flavonoid compound abundantly present in citrus fruits and has the potential to treat respiratory disorders. However, the clinical therapeutic effect of NRG is limited by its low bioavailability due to poor solubility. To enhance the solubility, naringenin nanosuspensions (NRG-NSps) were prepared by applying tocopherol polyethylene glycol succinate (TPGS) as the nanocarrier via the media-milling method. The particle size, morphology, and drug-loading content of NRG-NSps were examined, and the stability was evaluated by detecting particle size changes in different physiological media. NRG-NSps exhibited a flaky appearance with a mean diameter of 216.9 nm, and the drug-loading content was 66.7%. NRG-NSps exhibited good storage stability and media stability. NRG-NSps presented a sustainable release profile, and the cumulative drug-release rate approached approximately 95% within 7 d. NRG-NSps improved the antitussive effect significantly compared with the original NRG, the cough frequency was decreased from 22 to 15 times, and the cough incubation period was prolonged from 85.3 to 121.6 s. Besides, NRG-NSps also enhanced expectorant effects significantly, and phenol red secretion was increased from 1.02 to 1.45 μg/mL. These results indicate that NRG-NSps could enhance the bioavailability of NRG significantly and possess a potential clinical application.